Evolução da paisagem e cenários para conservação da biodiversidade do entorno da Floresta Nacional de Passo Fundo, Mato Castelhano, RS - Scariot, Eliziane Carla (2014)
The investigation of land use changes as a result of pressure from anthropogenic processes, is a tool for establishing correlations between spatial and temporal patterns and ecological processes of the landscape, being adequate for management of the surrounding protected areas. The Conservation Units surrounding_s in Brazil require measures that complement conservation strategies adopted only for the limits of the protected areas. The bu_er zones of conservation units surrounding has not yet received the attention needed to meet the objectives of in situ conservation. The general aim of this work was to analyze and quantify the land use dynamic and fragmentation process of natural vegetation, analyze the ecological sustainability and delineate scenarios for biodiversity conservation in the Passo Fundo National Forest surrounding, in the period 1986 to 2011, in order to generate information to management and implementation of conservation measures. Land use maps were made from Landsat image 5 of 12/09/1986, 08/09/1997 and 01/09/2011, orbit 222, 79 and 80 points. The mapping was done by visual classi_cation in software Mapinfo 10.0. The natural vegetation fragmentation process in 1986, 1997 and 2011 was analyzed from the elaboration of thematic maps of natural vegetation, and application of the landscape metrics in software Fragstats 4.1 (number of fragments, mean area of the fragments, proportion of natural area in the landscape, and degrees of isolation /connectivity and complexity of shapes of the patches). Ecological sustainability was assessed by using naturalness / urbanity (IB), environmental quality of fragments of natural vegetation (IQABIO) and environmental vulnerability (VAT-P) indicators, whose equations were calculated using the Idrisi software Selva. With environmental quality and naturalness and natural vegetation indicators were selected fragments of the study area with higher naturalness and quality to delineate a biodiversity conservation scenario for the Flona-PF surrounding. The results showed that the direct and indirect drivers of landscape change are respectively the agricultural activities, urbanization and conict with the local indigenous community. From 1986 to 2011 there was a reduction in the areas occupied by human activities and an increase in the proportion of natural areas. The average size of fragments or patches of natural vegetation increased, and the isolation distance between the fragments decreased in 2011, compared to previous periods (1986 and 1997). The indicators (IB, IQABIO and VAT-P) pointed Flona-PF and neighboring fragments as the areas with higher environmental quality, naturalness and less vulnerability. However, the vulnerability analysis (VAT-P) take into account only the direct forces changes of landscape changes disregarding the indirect forces as the demand of land by the local indigenous community, which can cause changes in this conservation area, including change of category. The results show a tendency to decrease the direct forces of landscape change for the Flona-PF surrounding during 1986 to 2011.